Effect of Tematic Learning Inquiry Method Based on Peer Assessment on Activity and Result Learning Student Grade IV - Nursidik, Nursidik; Supardi, Kasmadi Imam; Purwati, Eko (Universitas Negeri Semarang, 2017)
The purpose of this study was to analyze the influences of thematic learning of inquiry method based on peer assessment on activity and result of student learning of class IV. This type of research used true experimental with pretest-posttest control group design. The subjects of the study were fourth grade students of SD Negeri 01 Sidosari, Pekalongan. Based on the results of analysis of research data after getting treatment in the experimental class, and the control class was not treated with the prerequisite test of normality and homogeneity. The parametric statistic test used t-test analysis (one party) was obtained tcount = 0, 001> ttable = 0, 005 and the result of student activity analysis obtained tcount = 0, 002> ttable = 0, 005. Thus it can be concluded that inquiry method based on peer assessment has an effect on student activity and result of student learning. The suggestion of this study takes into account time allocation, attention to student activity, peer assessment based inquiry method is not only limited to thematic learning.